Therapeutic potential of Cissus quadrangularis Linn. (Veldt grape) in osteoporosis and arthritis: A scoping review of preclinical evidence - Poojitha Sri Sai Parinam, Radhika Prashant Hedaoo, Mansi Patil, Anuja Mohile, Nalini Khatwani, Archana Aainapure (Journal of Applied Pharmaceutical Science, 2025)
Cissus quadrangularis Linn. (CQ) is traditionally used for bone healing. Recent preclinical studies suggest its potential for managing osteoporosis and arthritis due to its bioactive compounds. This review evaluates CQ’s therapeutic mechanisms, optimal dosage, and long-term effects in animal models. A systematic literature search was conducted across PubMed, SCOPUS, JSTOR, and Web of Science, focusing on English-language animal studies from 2003 to 2024 (osteoporosis) and 2010–2024 (arthritis). Inclusion criteria required studies assessing bone health following CQ administration, while human studies, reviews, non-English publications, and accidental fracture studies were excluded. Among 294 identified articles, 37 met the criteria—23 for osteoporosis and 14 for arthritis. CQ’s bone-healing properties are attributed to β-sitosterol, lupeol, and vitamin C. Different formulations, such as bone-strengthening polyherbal supplements and sustained-release tablets (SRTs), demonstrated significant bone-protective effects. A dosage of 25 mg CQ in 100 mg SRT increased serum alkaline phosphatase, calcium, and phosphorus levels, while 405 mg/kg enhanced trabecular thickness and reduced osteoclastogenesis. CQ extracts (300–500 mg/kg) improved joint health by mitigating oxidative stress and pro-inflammatory cytokines. CQ exhibits promising anti-osteoporotic and anti-arthritic effects in preclinical models. However, well-designed clinical trials are necessary to confirm its efficacy and safety in humans for potential therapeutic applications.
Keywords: Cissus quadrangularis, veld grape, anti-osteoporosis, anti-arthritis, Senegal, traditional medicine, herbal supplement, phytochemicals